Enhancing Service Quality Through Digital Learning: Evidence from Typsy-Based Training in the Hotel Industry - Yohanes Agung Puji Triraharjo; Kadek Wiweka; Lioe Lyly Soewarni (Eduvest - Journal of Universal Studies, 2026)
The hospitality industry increasingly adopts digital learning platforms to improve employee capabilities and maintain service quality. However, empirical evidence regarding the relationships among digital training effectiveness, learning engagement, employee competence, and service quality remains limited, particularly within hotel organizations. This research investigates the influence of the perceived effectiveness of Typsy-based training on learning engagement, employee competence, and service quality among employees of Swiss-Bel hotel Bogor. A quantitative explanatory approach was employed using a cross-sectional survey design. Data were collected from 100 hotel employees who actively used the Typsy digital learning platform. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS. The findings reveal that the perceived effectiveness of Typsy-based training significantly influences learning engagement and employee competence. Learning engagement also has a positive effect on employee competence, while employee competence demonstrates the strongest influence on service quality. The results indicate that digital training effectiveness contributes both directly and indirectly to service quality through the development of employee competence. This study extends the literature on digital workplace learning and hospitality human resource development by demonstrating the importance of employee engagement and competence as mechanisms linking digital training to service outcomes. The findings also provide practical implications for hotel managers seeking to utilize digital learning platforms as strategic tools for competency development and service excellence.